Juozas Urbsys in the KGB spotlight. Source Outcrops - Veilentienė, Audronė (Genocidas ir rezistencija, 2020)
After occupying Lithuania, the Soviet Union first arrested and imprisoned members of the Lithuanian government and later other government operatives. Lithuanian Foreign Minister Juozas Urbsys spent 13 years in prisons in Tambov, Saratov, Moscow, Kirov, Gorky, Ivanov, Vladimir, and spent 11 of those years in solitary confinement. After Stalin’s death, the cases of political prisoners were reviewed. In 1954, J. Urbsys and Mrs. M. Urbsys were released from prison, and returned to their homeland in 1956. Urbsys had to live on a pension of 50 rubles and translations from the French language, which were commissioned by the Fiction Publishing House. After returning from prisons and The Gulag, former Lithuanian state figures, including J. Urbsys, were monitored by KGB agents, and they were subjected to various sanctions to compel the service of Soviet propaganda and to denigrate the achievements of an independent Lithuania.The historically in this issue is extremely limited – the testimony of J. Urbsys, about the confiscation of Klaipeda from Lithuania in the trial organized by the Berlin High ranking Hitlerite Officer Hans Globke, was the main focus. The main source of the investigation is the first time in Lithuanian history of the use of J. Urbsys’ records of visits by KGB employees and journalists carrying out their tasks, and publishing staff. The former minister wrote in calendars and notebooks information on the visits and suggestions of such visitors. Chronology of inscriptions were from 1960 to 1978. The chronological gaps in events were filled in with the memories of the people who knew Mr Urbsys.• Urbsys was in the KGB spotlight throughout the soviet occupation. After returning from prison, living in very poor conditions, J. Urbsys under the pressure of the KGB, was forced to write articles slandering independent Lithuania and exalting the life of Soviet Lithuania. Initially, KGB staff applied direct pressure, visiting Mr Urbsys’ house or inviting him to come to the KGB palace. KGB staff suggested that J. Urbsys, using the help of Solomon Atamuk and Boleslov Baranrak, wrote an article in the press “About the achievements of Soviet Lithuania with comparisons to the period of independent Lithuania”. Boleslovas Baranauskas, a former NKVD/KGB investigator, at the time presided over the special version of the publication of archival documents, which was established in early 1959 by the LKP CK, the purpose of which was to compromise former state figures and participants of the anti-Soviet resistance movement in the press.• Urbsys refused to write the articles, but agreed to testify live in an international court in Germany and to give an interview about the confiscation of Klaipeda from Lithuania, because he understood that these testimonies were useful and would not be distorted by the Soviet authorities. The former minister was also followed up by KGB agents, who were deployed to take an interest in the publishing of Mr Urbsys’ articles, to ask questions about writing memoirs. Former state figures sought to write memoirs in which they wanted to treat historical events from the positions of Lithuanian statehood, and the KGB sought to stop this process by strengthening the agency’s work.In order to force Mr Urbsys to write an article useful to Soviet propaganda, the KGB also used the services of journalists, the heads of the Kaunas Executive Committee or Soviet intelligence agents under the guise of Soviet “diplomats”. As an experienced diplomat, Mr Urbsys sought to treat them diplomatically, but at the same time adhere to his principles. This helped him avoid compromising other former national figures (e.g. Z. Toliusis) with the KGB in the press.The purpose of this article is to show for what purpose and methods the KGB attempted to use the last Lithuanian Minister of Foreign Affairs, Juozas Urbsys, to reveal what tactics the former foreign minister followed in order not to become a tool of the KGB.
Keywords: KGB; agents; political prisoners; repressions; Juozas Urbšys; soviet propaganda